The Association of Knowledge Management, Organization Culture, and Innovation with Organizational Performance: A Case at Study Institute Research XYZ - Navik Puryantini; Rofikotul A.; Dian Shinta P.; Bambang Tjahjadi (Jurnal Akuntansi dan Keuangan, 2018)
The purpose of this study was to analyze the impact of variable mediation knowledge management innovation in relation to organizational performance and analyze the impact of innovation on the relationship mediating variables of organizational culture on an organization. Population performers in this study were employees of XYZ. Collecting data in this study was conducted using the questionnaire method. Data analysis method used in this study is Partial Least Squares is a powerful method of analysis because it does not assume the data must use a certain scale and can use a small sample. The results showed that (1) knowledge management influence on innovation; (2) The effect on the organizational culture of innovation; (3) Knowledge Management of an effect on the performance of the organization; (4) The organizational culture influence on organizational performance (5) innovation does not affect the performance of the organization, (6) the innovation did not mediate the relationship of knowledge management to organizational performance; (5) innovation does not mediate the relationship of organizational culture on organizational performance. Results obtained interviews innovation does not affect the performance of the organization for their gaps and differences in perception between the authority and powers of innovation, so that innovation is always dependent on the individual who is willing to turn these innovations.